Enablers and Barriers to Circular Economy adoption in B2B Operations The Case Study of Refurbished Spare Parts and its B2B Customer relations in the European Region - Soriano, Maria (My University, 2026)
The industrial sector such as maritime industry is transitioning to circular economy. Circular prac-tices are under growing regulatory and environmental pressure to be adopted by the maritime industry. Refurbishment of spare parts is a viable alternative that can be adopted in the case of engine manufacturers to reduce the lifecycle emissions and the material consumption. Despite this potential, implementation in the industry is inconsistent, and the variables that affect custom-er acceptance have yet to be comprehensively defined. Through the context of a leading marine engine manufacturer and its B2B customers, this research identifies the specific enablers and barriers influencing the purchase of refurbished parts. Qualita-tive case study research design has been implemented for this research. Primary data was gath-ered through semi-structured interviews with five (5) sales managers from the marine engine manufacturing company. The sales managers served as expert sources who possess both technical knowledge about the products and the customer’s behavioral responses. Key findings indicate that nature of business, nature of products and technological factors as signif-icant enablers for ship owners and operators. Financial factors and regulatory factors worked as two-fold dimensions, both a driver and a barrier. Environmental and external stakeholders were neutral, and they were neither facilitators nor hindrances. They were required to have conditions of context that gave the necessary stability to run the initiative. However, social or cultural factors acted as primary barriers. The research concludes that in order to make the buying of refurbished parts successful, the firm will need to adopt a number of important organizational strategies. To begin with, the company should include the offers of refurbished in all quotes. They also have to enhance marketing and communication with customers and carry out root-case analysis of damaged parts systematically. In order to scale these operations, the company must increase world refurbishment centers and get access to technical drawings of spares in other manufacturing companies. Moreover, it is criti-cal to develop a running-hours monitoring system of refurbished parts. Lastly, the plan must in-volve focusing on older engine models and warranty extension of refurbished spares.
Keywords: circular economy; adoption; remanufacturing; manufacturing industry; business-to-business commerce; spare parts; marine technology; enterprises; industry; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development